POINT OF USE GRANULAR ACTIVATED CARBON FILTERS (POU) EFFICIENCY FOR ATRAZINE REMOVAL - Isaac, Ricardo de Lima; Fernandes, Roberto (Multi-Science Journal, 2018)
Atrazine is a concerning water sources contaminant that can remain at the drinking water. The objective of this study is to evaluate the efficiency of point of use (POU) filters with granular activated carbon to remove the contaminant, when added to deionized and natural well water under the theoretical concentrations of 1000.0 ng.L-1. The procedure used to quantify atrazine was the High-Performance Liquid Chromatography (HPLC), preceded by pre-concentration of the contaminants by solid phase extraction (SPE). Coconut carbon was evaluated, through preliminary tests carried out in "jar test" equipment, in order to obtain kinetic parameters, according to Freundlich equation. The parameters were inserted into a design model used in a complementary phase of the study, which evaluated the efficiency of filter prototypes in the removal of the contaminant in dynamic conditions. The results showed that the prototype filter, constructed from 90.0 g of coconut coal, which presented the highest efficiency for the removal of target pollutant in the preliminary trials, were able to reduce average 57.2% of atrazine after 1000.0 liters filtered, under predetermined operating conditions: flow rate 100 L.h-1 in continuous test. The filter prototypes were designed from the following Freundlich isotherms coefficients: qmax = 40.4 ng atrazine / mg carbon (maximum adsorption capacity); 1/n = 0.5138 and KF = 1.10, with correlation coefficient of 0.9960.